Strategi Manajemen Waktu Ibu Rumah Tangga dengan Parasocial Relationship dalam Perspektif Syariat Islam: Time Management Strategies of Homemaker Women with Parasocial Relationships in the Perspective of Islamic Sharia - Martareza, Arini Sabeela; Kumaini, Ruston (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The phenomenon of increased involvement of homemaker women in parasocial relationships serves as the background for this research, which poses challenges in managing domestic time. The Nineties Teume community is a fan group of the South Korean boy band Treasure, where the majority of its members are housewives. The aim of this study is to identify the factors causing homemaker women in the Nineties Teume community to engage in parasocial relationships, to analyze the time management strategies they employ, and to examine Islamic perspectives on the phenomenon. This research uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews, documentation studies, and comprehensive literature reviews. The results indicate that parasocial relationships develop as a coping mechanism for stress, personal entertainment needs, and recreational fulfillment through music media; common time management strategies include optimizing leisure time, implementing flexible schedules, prioritizing family and domestic tasks, practicing pragmatic multitasking, receiving support from family members, and adjusting to time-related challenges. From an Islamic perspective, this phenomenon is criticized because it tends to idolize nonmuslim figures and listen to music that contradicts Shari’ah values.